'Burning Violin': The Medically Important Spider Genus Loxosceles (Araneae: Sicariidae) in Iran, Turkmenistan, and Afghanistan, With Two New Species. Issue 2 (10th December 2020) - Zamani, Alireza; Mirshamsi, Omid; Marusik, Yuri M
Abstract: The taxonomic status of the medically important spider genus Loxosceles Heineken et Lowe, 1832 (Sicariidae) in Iran, Turkmenistan, and Afghanistan is revised. Two species are described as new to science: Loxosceles coheni sp. n. ( ♂ ♀, southwestern Iran) and Loxosceles turanensis sp. n. ( ♂ ♀, southern Turkmenistan and eastern Iran). Additionally, Loxosceles alicea Gertsch, 1967 syn. n. (♀, Peru) is synonymized with Loxosceles rufescens (Dufour, 1820). The local distribution of all treated species is mapped (including several new records), and reported cases of loxoscelism from this region are briefly reviewed.